Impacts of Domestic Savings and Domestic Investment on Economic Growth: An Empirical Study for Pakistan - Rahman, Md Zamilur; Ferdaus, Jannatul (Journal of Social Economics Research, 2021)
The purpose of this paper is to ascertain the dynamic impacts of domestic savings and domestic investment on economic growth of Pakistan by using annual data spanning from 1973 to 2018. After being confirmed that all the variables are stationary at first difference and have long-run cointegrating association, this study employed Dynamic Ordinary Least Squares (DOLS) approach to estimate long-run elasticities. The empirical findings reveal that domestic savings are negatively and domestic investment is positively associated with economic growth in Pakistan. In a nutshell, the results convey that domestic savings are dampening the economic growth figures and domestic investment is contributing to economic growth figures of Pakistan. The results of causality analyses report bidirectional causal link between domestic savings and economic growth and a unidirectional causal association between economic growth and domestic investment. Based on these empirical findings some policies are recommended to accelerate economic growth and for the long term sustainability of economic growth in Pakistan.